EFEKTIVITAS KONSENTRASI DAN LAMA PERENDAMAN AIR KELAPA TERHADAP VIABILITAS BENIH TERONG (Solanum melongena L.) KADALUARSA - Jumayrah, Jumayrah; Ardaniah, Ardaniah; Arsela, Primadiyanti (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Eggplant seeds that have deteriorated can still be utilized as planting material through invigoration treatment to improve viability and vigor. This study aimed to determine the effectiveness of invigoration materials and soaking duration on the viability of expired eggplant seeds (Solanum melongena L.). The research employed a Randomized Block Design (RBD) with two factors: invigoration materials consisting of air conditioning water (k1), 25% coconut water (k2), and 50% coconut water (k3); and soaking duration of 2 hours (l1), 4 hours (l2), and 6 hours (l3). Results showed that invigoration materials had a highly significant effect on the number of germinated seeds, germination time, sprout length, germination percentage, germination rate, and germination speed, while soaking duration significantly affected sprout length. The interaction between the two factors had no significant effect. The best treatment was 25% coconut water with 4 hours soaking, effectively invigorating expired eggplant seeds for use as planting material.